Impact of marketing communication strategies on consumers' acceptance and brand equity in Malaysian fertilizer industry. - Ammar Redza, Ahmad Rizal; Hasnida, A. W.; Shahrina, M. Nordin; Lai, F. W.; Hasrina, M. (American-Eurasian Network for Scientific Information (AENSI Publisher), 2014)
The agriculture sector has a profound effect on Malaysian people, economy and environment. Studies show that communication plays an important role in agricultural industry, helping agriculture businesses such as fertilizer manufacturers/suppliers to grow and prosper, builds relationships, strengthens the effectiveness of organization and allows farmers to learn about one another. Knowledge on agronomic factors is also one of the important factors for the farmers in increasing productivity. Farmers can be educated and valuable information can easily be transferred through accurate communication channels and it is important to educate farmers with up-to-date and relevant information. The fertilizer industry, on the other hand, is faced with numerous challenges with regard to communication. This conceptual paper is intended to look into the marketing communication strategies employed by the fertilizer industry in Malaysia in order to communicate with the farmers. This study also enhances the understanding on the relationship of marketing communication strategies on consumers' acceptance and brand equity. Several hypotheses are developed and recommendations for future studies are proposed.